mTOR-Mediated Regulation of Immune Responses in Cancer and Tumor Microenvironment - Mafi, Sahar; Mansoori, Behzad; Taeb, Shahram; Sadeghi, Hossein; Abbasi, Reza; Cho, William C.; Rostamzadeh, Davoud (Frontiers in Immunology, 2022)
The mechanistic/mammalian target of rapamycin (mTOR) is a downstream mediator in the phosphatidylinositol 3-kinase (PI3K)/Akt signaling pathways, which plays a pivotal role in regulating numerous cellular functions including cell growth, proliferation, survival, and metabolism by integrating a variety of extracellular and intracellular signals in the tumor microenvironment (TME). Dysregulation of the mTOR pathway is frequently reported in many types of human tumors, and targeting the PI3K/Akt/mTOR signaling pathway has been considered an attractive potential therapeutic target in cancer. The PI3K/Akt/mTOR signaling transduction pathway is important not only in the development and progression of cancers but also for its critical regulatory role in the tumor microenvironment. Immunologically, mTOR is emerging as a key regulator of immune responses. The mTOR signaling pathway plays an essential regulatory role in the differentiation and function of both innate and adaptive immune cells. Considering the central role of mTOR in metabolic and translational reprogramming, it can affect tumor-associated immune cells to undergo phenotypic and functional reprogramming in TME. The mTOR-mediated inflammatory response can also promote the recruitment of immune cells to TME, resulting in exerting the anti-tumor functions or promoting cancer cell growth, progression, and metastasis. Thus, deregulated mTOR signaling in cancer can modulate the TME, thereby affecting the tumor immune microenvironment. Here, we review the current knowledge regarding the crucial role of the PI3K/Akt/mTOR pathway in controlling and shaping the immune responses in TME.